Domains of entrepreneurial ecosystem and its impact on entrepreneurship - Aryal, Anil Kumar (Journal of Business and Social Sciences, 2021)
Entrepreneurship is the key determinant for economic growth because it maximizes wealth of the nation by creating new businesses based on innovation and disruptive ideas. The success of entrepreneurial venture relies on proper understanding of its ecosystem, i.e., various elements or factors associated with entrepreneurship. This paper has tried to uncover various elements of the entrepreneurial ecosystem based on the model developed by Isenberg in 2010 and how they impact on entrepreneurship. This is a literature based reflective article where various literatures are referred to link the connection between entrepreneurship and its mainly six domains: Policy, Finance, Culture, Support, Human Capital, and Markets. Literatures have shown the strong relation and impact of these domains on entrepreneurial activities but to clear the level of impact, further studies are necessary. Similarly, there is also an avenue to explore the connectivity between these domains itself.